Education after Dewey - Fairfield, Paul, 1966- (New York : Continuum, 2012)
'This study re-examines John Dewey's philosophy of education, and asks how well it stands up today in view of developments in Continental European philosophy' -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Dewey, John, -- 1859-1952 -- Influence; Education -- Philosophy; Democracy and education; Continental philosophy